Implementasi Pendidikan Islam Merdeka Belajar Berbasis Media Sosial - Andriani, Monik; Bustam, Betty Mauli Rosa (LPPM Institut Nasional Laa Roiba Bogor, 2024)
The existence of technological advances requires educators to be able to adapt in implementing social media-based learning. However, in practice there are still educators who do not understand how to implement social media as a supporting tool in the process of learning activities. Therefore, the importance of education regarding the implementation of social media in learning. The aim is to find out how to implement social media-based Islamic education learning in independent learning. This research is a qualitative research using descriptive analysis techniques with library research. Through this literature review, the researcher tries to describe existing phenomena, which are taking place now or in the past and are sourced from various sources that have theoretical depth from experts. The results of this study show that in implementing Islamic Education learning in the era of independent learning it is very necessary because in accordance with independent learning students and teachers are given freedom in implementing learning, this is very much needed for the role of social media in supporting the learning process of independent learning. The results of this study have implications for the use of social media for teachers in supporting teaching and learning activities in the era of independent learning. Keywords: Social media, Islamic Education, Freedom to learn